EME financial conditions: Which global shocks matter? - David Lodge; Ana-Simona Manu (European Central Bank (ECB), 2019)
This paper provides a quantitative assessment of the relative importance of global structural shocks for changes in financial conditions across a sample of emerging market economies. We disentangle four key drivers of global financial markets (oil supply shocks, global economic news shocks, US-specific economic news shocks and US monetary shocks) and show that these global factors account for about half of the variation in risky asset prices across EMEs. The influence of global factors for EME interest rates and currencies is much smaller, suggesting that factors beyond the identified global shocks (e.g. domestic or regional shocks) might be more important. In contrast to the recent literature on the global financial cycle which has emphasised the prominent role of US monetary policy, we find that although US monetary shocks have some influence in shaping EME financial markets, the broader global environment plays a significantly stronger role.
Keywords: E44; E52; G15; 330; global shocks; international financial markets; asset prices; financial conditions; emerging markets; spillovers